Observing Pressured Sea Ice in the Hudson Strait Using RADARSAT: Implications for Shipping - Mussells, Olivia (Université d'Ottawa / University of Ottawa, 2015)
Pressured and ridged ice is a dangerous hazard facing ships in the Arctic. Ships can become stuck or beset in these conditions, which is environmentally and economically costly. Understanding where and when ridges form as a result of pressured ice is important for ensuring safe winter shipping operations; however there have been few studies to date regarding the distribution of ridges and their impacts within a geographic region. The Hudson Strait, which connects Hudson Bay and the Atlantic Ocean, is the site of ongoing winter shipping, where vessels frequently encounter pressured ice. This thesis addresses two questions: where and when do ridges occur in the Hudson Strait and what are their impacts on an ice strengthened vessel traveling through the Strait. To answer the first question, ridges were manually identified in RADARSAT-1 and -2 images during the winter months (December to May) from 1997-2012. Ridge counts and densities for each winter season were calculated and their spatial distribution was mapped. A 30-year sea ice climatology of the Hudson Strait was also created in order to understand ongoing trends in freeze-up and breakup timing in the region. Recurring patterns in the location and timing of ridging were found in the Hudson Strait, specifically in areas where shearing and bottlenecks created pressure. Ridge densities were correlated with sea level pressure, air temperature and wind NCEP reanalysis data to look to for connections between these factors and ridge densities. Some connections were found between freeze-up dates, sea level pressure and ridge densities. The second half of this thesis focuses on how ridges impact the voyage of an ice-strengthened vessel. Log books from the MV Arctic, a cargo ship that makes two winter transits through the Hudson Strait every year, were used to plot the movement of the ship and where and when it became beset. These data were examined for temporal and spatial patterns in besetting events. Most besetting events took place in February and March. They typically occurred in the eastern and western ends of the Strait. These voyages were compared to ridge data from the first half of thesis, and there were good correlations between the presence of high ridge densities and ship besetting events, demonstrating that ridge densities identified in satellite imagery can act as a proxy when forecasting hazardous ice conditions. This research fills an important knowledge gap in understanding where and when pressured ice forms in the Hudson Strait and what factors play a role in creating this hazardous ice condition. It also addresses the impacts that ridges have on ship transits through the Strait.